Problematika Pendirian Rumah Ibadat Umat Minoritas di Kalimantan Selatan - Bayani Dahlan; Rabiatul Aslamiyah (UIN Antasari Banjarmasin, 2022)
This article describes how problematic the construction of houses of worship for minorities is in South Kalimantan. This article is the result of field research with a qualitative approach and used observation, interviews, and documentation as data collection techniques. This finding state that the causes of conflicts over the construction of houses of worship for minorities in South Kalimantan are motivated by several factors, namely the different interpretations of regulations and regulations that are not fully representative. Another cause is socio-religious factors, namely, the majority of people reject the existence of houses of worship of other religions in their vicinity, some even have the view that approving the establishment of houses of worship of other religions is not justified in the Islamic faith, and is not an area of tolerance. Another factor is the politicization of religion in the contestation of regional head elections (Pilkada) and legislative elections (Pileg). Another cause is marriage due to a change of religion which raises suspicion among religious communities. These factors occurred in the construction of the Indonesian Bethel Church (GBI) of Pasir Mas, Banjarmasin City, and the Guan Te Temple, Persada Mas Complex, Banjar Regency.